Group Affiliation and Entry Barriers: The Dark Side Of Business Groups In Emerging Markets - Pattnaik, Chinmay; Lu, Qiang; Gaur, Ajai S. (2018)
Business groups dominate the economic landscape in many economies around the world. While business groups overcome the institutional voids arising due to inefficiencies of external markets, they also possess market power, which could be economically and socially counterproductive, especially for unaffiliated firms. Drawing on the transaction cost and industrial organization economics, we examine whether the presence of business group affiliated firms in industries restricts the entry of unaffiliated firms or firms affiliated with small- and medium-size business groups. Findings based on Indian firms suggest that investments by business group affiliated firms in an industry have an inverted U-shaped relationship with the investment by unaffiliated firms. However, investments by firms affiliated with large-sized business groups have a U-shaped relationship with the investment by affiliates of small and medium business groups. These findings suggest that the market power of business groups and entry barrier relationship is contingent on the size of the business groups.
Keywords: India; Institutional void; Market Power; Entry barrier; Business groups